Hydraenidae of Madagascar (Insecta: Coleoptera) - Perkins, Philip D. (Zootaxa, 2017)
The Madagascar fauna of the beetle family Hydraenidae is comprehensively revised, based on the study and databasing of 6,949 specimens. New collection records are provided for 11 previously described species, and 95 new species are described. Three new subgenera of Hydraena, viz. H. (Micromadraena), H. (Monomadraena), and H. (Dnahydnaedna) are described, and several new species groups of Hydraena are diagnosed. Two new genera in the tribe Madagastrini are described: Menomadraena and Trinomadraena. The Malagasy hydraenid fauna now comprises 106 species arrayed in the following nine genera: Aulacochthebius (2), Hydraena (65), Limnebius (10), Madagaster (8), Menomadraena (6), Ochthebius (1), Protozantaena (5), Sicilicula (8), and Trinomadraena (1). Lectotypes are designated for the following species: Aulacochthebius plicicollis (Fairmaire), 1898 (Ochthebius); Hydraena dilutipes Fairmaire, 1898; Hydraena impressicollis Fairmaire, 1898; Hydraena marginicollis Regimbart, 1903 (= Hydraena regimbarti Zaitzev 1908; nomen novum); and Ochthebius alluaudi Regimbart, 1903. Hydraena discicollis Fairmaire, 1898, is considered a nomen dubium: no type specimens were found, and the description appears to be that of a species of Aulacochthebius or Ochthebius, not Hydraena. High resolution digital images of lectotypes and holotypes of new species are presented (online versions in color). Male genitalia, representative antennae, maxillary palpi, and female terminal abdominal segments and spermathecae are illustrated. Geographic distributions of all species are mapped. Possible colonization and vicariance events are discussed at the tribal, generic and species group levels. The tribe Madagastrini, found only in Madagascar and southern India, is hygropetric, indicating that this microhabitat type has been continuously present in both Madagascar and India at least since the two separated, currently estimated to be 88 million years ago. Contrastingly, some lowland lentic species of other genera appear to be closely related to species in southern Africa, suggesting rather recent colonization events. New species of Aulacochthebius: A. perlaevis (Mahajanga, Boeny: Mahavavy Kinkony RS). New species of Hydraena (Micromadraena): H. breviceps (Fianarantsoa, 29 km SSW Ambositra, Ankazomivady); H. fortipes (Antsiranana, Forêt d' Antsahabe); H. genuvela (Antsiranana, Forêt de Binara); H. parvipalpis (Antananarivo, Réserve Spéciale d'Ambohitantely); H. rubridentata ((Mahajanga, Parc National de Namoroka); H. serripennis (Antsiranana, Forêt d' Antsahabe). New species of Hydraena (Monomadraena): H. acicula (Antsiranana, Antsaba, Galoko Mountains); H. ambohitantely (Antananarivo, Ambohitantely Spec. Res.); H. amplexa (Fianarantsoa, Andringitra NP); H. amplipunctata (Fianarantsoa, 7 km W Ranomafana); H. antsahabe (Antsiranana, Forêt d' Antsahabe); H. bergsteni (Antsiranana, Diana: Beraty); H. bisinuata (Toamasina, Tamatave 6.3 km S Ambanizona); H. bisinuloba (Toliara, Menabe: Kirindy RS.); H. bispica (Toamasina, Alaotra Mangoro: Analamazoatra SR); H. casacolumna (Fianarantsoa, Andringitra NP); H. compacta (Antananarivo, Ankaratra, Reserve Manjakatompo); H. contracolorata (Antsiranana, Montagne des Francais); H. epipleurata (Antsiranana, Forêt de Binara); H. furcula (Toliara, 40km N of Fort Dauphin, Managotry); H. gereckei (Antananarivo, Ankaratra, Reserve Manjakatompo); H. goldschmidti (Antananarivo, Anjozorobe, Ravoandrina); H. inseriata (Antananarivo, Anjozorobe, Ravoandrina); H. jubata (Antsiranana, Sava Marojejy NP); H. levifurcata (Fianarantsoa, Namarona River, 7 km SW Ranomafana); H. lubrica (Antananarivo, Ambohitantely Spec. Res.); H. mahavavona (Fianarantsoa, Ionilahy, Mahavavona); H. manjakatompo (Antananarivo, Ankaratra, Reserve Manjakatompo); H. marojejy (Antsiranana, Parc National de Marojejy); H. multiarcuata (Fianarantsoa, Ranomafana); H. oscillata (Toamasina, Alaotra Mangoro Andasibe-Mantadia NP); H. parvispinosa (Toamasina, Andasibe NP); H. pentarubra (Antsiranana, Montagne d'Ambre); H. quatriloba (Toliara, Andohahela NP, Tsimelahy); H. ranomafana (Fianarantsoa, Ranomafana); H. ravoandrina (Antananarivo, Anjozorobe, Ravoandrina); H. rubrifurcata (Antsiranana, Sava, Marojejy NP); H. sculponea (Antsiranana, Befingotra (9.2 km WSW), Res. Anjanaharibe-Sud); H. simplicata (Antsiranana, Montagne d'Ambre); H. tibiodentipes (Fianarantsoa, Andringitra NP); H. triaequalis (Fianarantsoa, Ranohira); H. tripartita (Fianarantsoa, Ranomena); H. upsilonica (Toamasina, Zahamena NP); New species of Hydraena (Hydraenopsis): H. andranomena (Toliara, Andranomena); H. arta (Antsiranana, Parc National de Marojejy); H. bucollis (Toamasina, Tamatave, Andranobe Field Station); H. clavulata (Fianarantsoa, Ranomafana); H. contorta (Antananarivo, Anjozorobe forest reserve); H. dilutipoides (Mahajanga, Parc National Tsingy de Bemaraha); H. divisa (Antsiranana, Antsaba,Galoko Mountains); H. elementaria (Antananarivo, Tamatave, Coastal lagoon); H. fulgidicollis (Antananarivo, Parc de Tsimbazaza); H. longiloba (Fianarantsoa, Madiorano); H. nanula (Antsiranana, Ankarana, Ampositelo); H. orchisa (Toamasina, Alaotra Mangoro Andasibe-Mantadia NP); H. pilobova (Antsiranana, Sava, Marojejy NP); H. pilotumida (Fianarantsoa, 7 km W Ranomafana); H. ranarilalatiani (Toamasina, Alaotra Mangoro: Analamazoatra SR); H. randriamihajai (Antsiranana, Diana: Montagne d'Ambre NP); H. renalisa (Antsiranana, Sambava: Marojejy NP); H. sinuatipes (Antsiranana, Ankarana); H. torquata (Fianarantsoa, Andringitra NP). New species of Limnebius: L. angulatus (Fianarantsoa, Namarona River, 7 km W Ranomafana); L. balkei (Antsiranana, Montagne d'Ambre); L. bergsteni (Fianarantsoa, Namarona River, 7 km W Ranomafana); L. clandestinus (Mahajanga, Boeny:Mahavavy Kinkony RSc); L. labratus (Toamasina, Maroantsetra); L. lacrimosus (Toamasina, 18.7911S 48.4259E Alaotra Mangoro Andasibe-Mantadia NP); L. lobatus (Toliara, Manakaravavy); L. maximadus (Toamasina, Alaotra Mangoro: Analamazoatra SR); L. nanostillus (Antsiranana, Ankarana); L. steineri (Fianarantsoa, 7 km W Ranomafana). New species of Madagaster: M. barbata (Fianarantsoa, Andringitra NP); M. bergsteni (Antananarivo, 18.8704S 47.6708E Analamanga); M. cataracta (Antsiranana, Sava, Marojejy NP); M. procarina (Fianarantsoa, 32 km S Ambositra); M. quadricurvipes (Fianarantsoa, Andringitra NP); M. simplissima (Fianarantsoa, 32 km S Ambositra). New species of Menomadraena: M. andringitra (Fianarantsoa, Res. Andringitra); M. concava (Fianarantsoa, R.S. Ivohibe); M. fisheri (Toliara, Enakara (11 km NW), Res. Andohahela); M. ivohibe (Fianarantsoa, R.S. Ivohibe); M. nitedula (Fianarantsoa, Res. Andringitra); M. sembella (Fianarantsoa, Amparihibe). New species of Protozantaena: P. duplicata (Antananarivo, Vakinankaratra: Manjakatompo Stn. Forestière); P. elongata (Antananarivo, Vakinankaratra: Manjakatompo Stn. Forestière). New species of Sicilicula: S. ampla (Antananarivo, Onive River near Ilempona); S. bergsteni (Fianarantsoa, 21.2263S 47.3694E, Matsiara Ambony, Ranomafana NP); S. conjugalis (Fianarantsoa, Namarona River, 7 km SW Ranomafana); S. cordicollis (Fianarantsoa, Namarona River, 7 km SW Ranomafana); S. hygropetrica (Fianarantsoa, Matsiara Ambony, Ranomafana NP); S. malagasica (Fianarantsoa, Abohimahasoa); S. sexplanata (Antsiranana, Mt. Tsaratanana). New species of Trinomadraena: T. clusa (Antsiranana, Mt. d’Ambre).